Providing Health Education (Instagram Social Media Fasting) Against FoMO (Fear of Missing Out) Incidents in Adolescents at SMKN 2 Kediri - Lela Tri Wahyu Liana; Katmini; Wahyu Purnomo Jati (Journal of Hospital Management and Services, 2023)
FoMO (Fear of Missing Out) is a concern that occurs in individuals when they see other people doing social events or fun activities without them. This study aims to see the effect of providing health education (fasting on Instagram social media) on the incidence of FoMO in adolescents at VHS 2 Kediri.. The sample in this study amounted to 86 students. This study uses a quantitative pre-experimental approach with a research design of One Group Pre-Test-Post Test Design. The measuring instrument used is a questionnaire with a reliability value of 0.909 > 0.60. Bivariate analysis test using Paired Sample t-test. The results showed that the average value of the pre-test was 59 and the post-test was 47. While the results of the Paired Sample t-test showed that the value of sig (2-tailed) was 0.000 <0.05, then reject H0 and accept H1 so that it can be interpreted that there is an influence between the provision of health education (fasting on Instagram social media) on the incidence of FoMO. So it can be concluded that the provision of health education has an influence in reducing the symptoms of FoMO experienced by adolescent social media users with a span of 2 weeks.